PERHITUNGAN PERBANDINGAN SELISIH BIAYA PRODUKSI DENGAN MENGGUNAKAN MODEL DUA SELISIH DAN MODEL TIGA SELISIH - Susi Astuti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
The calculation of the difference between the cost of production or cost of production deviation calculation is one that aims to management. The calculation is one of the means of controlling production costs. Controlling the cost of production is by comparing the cost of a standard that has been set by the company with its actual cost. From these calculations, the management can determine the cost of parts that deviate both favorable or unfavorable nature and under thw control of anyone. And to know the control of production costs and the impact on gross profit of an enterprise Difference in cost of production is profitable if the costs of production standards set larger than te actual production cost. While the difference in the cost of production is not profutable I the costs of production standars set smaller then the actual prodction cost. CV Sumber Cahaya Abadi is one of the manufacturing company engaged in the production with output in the raffia and straw. This CV are mass produces raffia and straw in bulk and serve orders from customers in both the large and small parties. Therefore the company requires the calculation of the difference in production cost analysis that generates accounting information useful in controlling production costs. Recommendations can be given is monitoring the company must keep records of the cost of production in order to avoid further mistakes cost allocation and corporate presentation can further improve the control of production costs to profits by arranging periodic activity reports so that companies can get more optimal profits and had to check periodically to record the presentation of the allocation of costs in order to obtain maximum gross profit. Keywords : Production Cost, Analysis of the Diifference in Production Cost, Production Cost Control.